Clinical data analysis of telmisartan for hypertension management in Indian population - Prem Kumar, A (Bioinformation, 2021)
It is of interest to evaluate the clinical characteristics, treatment patterns, clinical effectiveness, and safety of telmisartan as a monotherapy or as part of combination therapy in Indian adults (>18 years old) with hypertension. All patients were receiving telmisartan as monotherapy, or as a combination therapy for hypertension management. Demographics, risk factors, existing comorbidity, and ongoing medical therapies were retrieved from the patients’ medical records. A total of 8607 patients with hypertension (median age, 51.0 years) were part of the study. The gender distribution suggested, 5534(64.3%) patients were male, and 3073 (35.7%) were female patients. The excess salt intake (39.0%) was the most common risk factor according to the results. The analysis revealed telmisartan dual therapy (57.9%) as the most prescribed therapy, followed by monotherapy (32.5%), and triple therapy (9.6%). Further, telmisartan 40mg (21.3%) and telmisartan 40mg plus amlodipine 5mg (17.6%) were the most commonly prescribed therapies. The data suggested that only 17.2% of patients required dose titration. The mean systolic blood pressure (SBP) and diastolic blood pressure (DBP) (mmHg) were significantly decreased with monotherapy (mean change: 19.8 [15.1] mmHg and 8.8[8.2] mmHg), dual therapy (mean change: 23.7 [16.6] mmHg and 10.3[8.5] mmHg), and triple therapy (mean change: 28.6 [19.0] mmHg and 12.1[10.8] mmHg) after the treatment (P<0.001). A total of 98.4% of the patients were compliant, and 97.6% achieved the target blood pressure goal with telmisartan-based therapy. There were 157 adverse events reported altogether. The Physicians’ global evaluation of efficacy and tolerability showed the majority of the patients receiving telmisartan-based therapy on a good to excellent scale. Telmisartan used as a monotherapeutic agent or as a part of combination therapy was successful and effective in reducing blood pressure and achieving the blood pressure target. Irrespective of the patient’s age, duration, and stages of hypertension, the study resulted in a good to excellent scale in efficacy and tolerability in the Indian patients having hypertension.